Mengulik Tradisi Tegal Deso Di Dusun Sukci Sebagai Simbol Perayaan Berdirinya Kabupaten Pasuruan - Wildhan Ichzha Maulana; Farida Dwitya Aninda; Sudrajat Sudrajat (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2023)
Tradition Tegal Deso is carried out every year on September 18 as well as a commemoration of the birth of Pasuruan Regency which is attended by all local people, coconut villages and their tools, humanists, spiritualists, and academics. The purpose of this research study is to find out the objectives, procedures for implementation, functions, and developments along with their setting as a symbol of the celebration of the founding of Pasuruan Regency. This study uses a qualitative approach and an ethnographic model supported by Niels Mulder's theory of the moral basis of Javanese society, while data analysis uses a triangulation pattern. The results of this study indicate that (1) the Tegal Deso in Dusun Sukci is a representation of the community's expression of gratitude. (2) The implementation of this tradition lasts for 3 days. (3) This tradition includes religious, socio-cultural, economic, and educational functions. (4) This tradition has developed, especially regarding the implementation time which is always undergoing adjustments, up to the most recent through Regional Regulation No. 8 of 2007 stipulated that September 18 is the time for the implementation of the Tegal Deso as well as a historical commemoration of the birth of Pasuruan Regency.